PERANCANGAN ARCHITECTURE ENTERPRISE UNTUK DINAS KEARSIPAN DAN PERPUSTAKAAN DAERAH SUKABUMI MENGGUNAKAN ENTERPRISE ARCHITECTURE PLANNING - Nita Eka Juliani (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2019)
The use of information technology in improving public services is a key requirement because it can create effective and efficient public services. The Sukabumi archive and library department is the assistant district head's office, which has the main task of managing the archive and library services. Servicesprovided by the Sukabumi Archive and Library Office include, inter alia, the use of archiving services, static archive services, dynamic archive services, and library collaboration services. The services provided by the Sukabumi Archive and Library Office so far still require a relatively long process because they are done manually such as monthly visitor reports while loan book reports still use Ms. Excel. EAP is a good methodology to be used in the initial stages in an enterprise architecture. Value chain analysis identifies four supporting activities and five main activities The design of SWOT analysis is very possible to be implemented based on the survey results and the results in quadrant 1 that shows the system in Growth condition, because the strength and opportunity factors are greater than the weaknesses and threats. EAP has clear stages in developing enterprise architecture that includes data architecture, applications and technology. From the results of the data architecture, a list of candidate data entities can be obtained that can propose 21 initial data for future purposes. From the technology architecture the definition of technology platform is obtained